Long-range correlations in the mechanics of small DNA circles under topological stress revealed by multi-scale simulation - Sutthibutpong, Thana; Matek, Matek; Benham, Craig; Slade, Gabriel G.; Noy, Agnes; Laughton, Charles A.; Doye, Jonathan P.K.; Louis, Ard A.; Harris, Sarah A. (Oxford University Press, 2016)
It is well established that gene regulation can be achieved through activator and repressor proteins that bind to DNA and switch particular genes on or off, and that complex metabolic networks deter- mine the levels of transcription of a given gene at a given time. Using three complementary computa- tional techniques to study the sequence-dependence of DNA denaturation within DNA minicircles, we have observed that whenever the ends of the DNA are con- strained, information can be transferred over long distances directly by the transmission of mechanical stress through the DNA itself, without any require- ment for external signalling factors. Our models com- bine atomistic molecular dynamics (MD) with coarse- grained simulations and statistical mechanical calcu- lations to span three distinct spatial resolutions and timescale regimes. While they give a consensus view of the non-locality of sequence-dependent denatura- tion in highly bent and supercoiled DNA loops, each also reveals a unique aspect of long-range informa- tional transfer that occurs as a result of restraining the DNA within the closed loop of the minicircles.